Cell suicide in starving hybridoma culture: survival-signal effect of some amino acids - Franěk, František (Kluwer Academic Publishers, 1997)
Two mouse hybridoma cell lines cultured in different basal media withthe iron-rich protein-free supplement were subjected to deliberatestarvation by inoculation into media diluted with saline to 50% or less.In the diluted media the growth was markedly suppressed and a largefraction of cells died by apoptosis. The cells could be rescued fromapoptotic death by individual additions of amino acids, such as glycine,L-alanine, L-serine, L-threonine, L-proline, L-asparagine, L-glutamine,L-histidine, D-serine, β-alanine or taurine. Amino acids withhydrophobic or charged side chains were without effect. The apoptosispreventing activity manifested itself even in extremely diluted media,down to 10% of the standard medium. The activity of L-alanine in theprotection of cells starving in 20% medium was shown also in semicontinuousculture. In the presence of 2 mM L-alanine the steady-state viable cell density more than doubled, with respect to control, andthe apoptotic index dropped from 37% in the control to 16%. It wasconcluded that the apoptosis-preventing amino acids acted as signalmolecules, rather than nutrients, and that the signal had a character ofa survival factor. The specificity of present results, obtained with twodifferent hybridomas, supports our view (Franěk and Chládková-Šrámková, 1995) that the membranetransport macromolecules themselves may play the role of therecognition elements in a signal transduction pathway controlling thesurvival of hybridoma cells.